Juvenile Idiopathic Arthritis and COVID-19 Pandemic: Good Compliance With Treatment, Reluctance to Return to School - Quéré, Baptiste; Lemelle, Irene; Lohse, Anne; Pillet, Pascal; Molimard, Julie; Richer, Olivier; Sordet, Christelle; Despert, Véronique; Rossi-Semerano, Linda; Borocco, Charlotte; Kone-Paut, Isabelle; Gervais, Elisabeth; et al. (Frontiers in Medicine, 2021)
Objective: The SARS-CoV-2 pandemic has induced an exceptional sanitary crisis, potentially having an impact on treatment continuation, for juvenile idiopathic arthritis (JIA) patients receiving immunosuppressive therapies. After national lockdowns, many patients were also concerned about their safety at school. We evaluated the impact of the pandemic on the optimal continuation of treatment and on the return to school in JIA patients. Methods: JIA patients under 18 years of age, usually treated with disease-modifying anti-rheumatic drugs (DMARDs) were prospectively included during their outpatient visit and completed a standardized questionnaire. The primary outcome was DMARD treatment modification in relation to the context of the pandemic but we also evaluated the pandemic's impact on the schooling. Results: One hundred and seventy three patients from 8 different expert centers were included between May and August 2020. Their mean age was 11.6 years (± 4.1 years), and most of them 31.2% (54/173) had a rheumatoid factor-negative polyarticular JIA. Fifty percent (86/172) were treated with methotrexate, and 72.5% (124/171) were treated with bDMARDs. DMARD treatment modification in relation to the pandemic was observed in 4.0% (7/173) of participants. 49.1% (81/165) of the patients did not return to school due to a personal/parental decision in 69.9% (55/81) of cases. Two patients were diagnosed positive for SARS-CoV-2 infection. Conclusion: This study suggests that JIA patients treated with DMARDs continued their treatment during the pandemic and were rarely affected by symptomatic COVID-19. In contrast, parents' reluctance was a major obstacle for returning to school. Therefore, more solidified school reopening strategies should be developed.